Developing understandings of 'inclusion' and 'inclusive schooling' - Bridge, Douglas James (Curtin University, 2002)
This thesis suggests that students with (dis)abilities are immersed in, and emerge from powerful discourses within classrooms named `inclusive'. It suggests that resilient and normative psycho-medical discourses and discourses of special education work to maintain the deep structures of schooling, and work against a valuing of difference, and of the Other, within schools and classrooms named `inclusive'. The inquiry that is the basis of this thesis works with textual representations of `inclusion' and `inclusive schooling' and works to address issues of identity and subjectivity within the various discourses from which `inclusion' and `inclusive schooling' might be understood to emerge. It is sited within Western philosophical streams concerned with language and meaning, discourse and narrative, texts and textuality. It emerges from a qualitative research paradigm and is deeply influenced by the earlier works of Michel Foucault (1969, 1970, 1972, 1991). Through these works Foucault develops `genealogy' as a form of historical analysis. This thesis engages genealogy as a form for critical interpretative inquiry into schooling practices named `inclusive' of students with (dis)abilities. The genealogy admits the historical, social, theoretical and political contexts which frame research, inquiry and interpretation within the social sciences. The inquiry emerges from an epistemology of tentativeness and uncertainty. It accepts that knowledge is contextual, contingent and indeterminate. It addresses the associated `crisis of representation' (Denzin & Lincoln 1994, 1998) related to what might constitute an adequate description of the sets of social relations and spaces named `inclusive schooling' through interpretative processes of opening questions and sets of questions.This genealogy develops understandings of `inclusion' and `inclusive schooling' through unfolding sequences of questions as 'thought-lines' that are strategies for this interpretative inquiry. Three thought-lines are woven from the questions which both propel, and emerge from, the processes of this critical interpretative inquiry: The 'self-other' thought-line; The 'included-excluded' thought-line; The 'particular-general' thought-line. Thought-lines transgress the borders of form and content in this inquiry. They are enmeshed to become the fabric of the genealogy. The thesis is in three sections, the first, Shaping a Genealogy, offers a theoretical and methodological perspective. The second, Squinting and Connecting, is in the form of a suite of interpretations, and the last, Developing Understanding, offers a range of ways in which inclusion and inclusive schooling might be understood. The thesis culminates in a set of new questions that represent a range of understandings of inclusion and inclusive schooling.